Previously licensed anti-mycobacterial drugs: a re-appraisal. - Ameen, Sirwan Muhsin Muhammed (Sulaimani Journal for Pure and Applied Sciences, 2016)
The discovery of antimycobacterial agent was the outcome of intensive efforts made between 1930 and 1970 to identify antimicrobial drugs. Sulfonamides (1930s), Streptomycin (1944) and Rifampicin (1965) are first and the last of the anti-mycobacterial drugs currently in use. Despite the availability of effective anti-tuberculosis chemotherapy, significant morbidity and mortality due to this disease continue to occur. The emergence and spread of multi-drug resistant (MDR) and extensively-drug resistant (XDR) strains of Mycobacterium tuberculosis has more complicated the problem of tuberculosis (TB) control and reduced the effectiveness of the current anti-TB drug. The present situation clearly demonstrates the need for a re-evaluation of our knowledge to treating TB and the current TB drugs. One of the highest achievements of modern medicine has been the development of antibiotics for the treatment of lethal infections. Unfortunately, the progress for new drugs against tuberculosis has been very inadequate over the past four decades. In the fight against emerging MDR and XDR resistance we can no longer rely completely on the finding of new antibiotics; we must also follow rational approaches to the use of older antibiotics such as sulfonamide. This review provides a concise historical of previously licensed drugs for treatment of tuberculosis and the targets and their mode of action of these drugs are briefly discussed.
Keywords: Mycobacteriumtuberculosis; antituberculosis drugs